Anticontractile effect of perivascular adipose tissue and leptin are reduced in hypertension - Beatriz eGálvez-Prieto; Beatriz eSomoza; Marta eGil-Ortega; Concha eF García-Prieto; Ana ede las Heras; María eGonzález; Silvia eArribas; Isabel eAranguez; Juliane eBolbrinker; Reinhold eKreutz; Mariano eRuiz-Gayo; María S Fernández-Alfonso (Frontiers Media S.A., 2012)
Leptin causes vasodilatation both by endothelium-dependent and -independent mechanisms. Leptin is synthetized by perivascular adipose tissue (PVAT). The hypothesis of this study is that a decrease of leptin production in PVAT of spontaneously rats (SHR) might contribute to a diminished paracrine anti-contractile effect of the hormone. We have determined in aorta from Wistar Kyoto (WKY) and SHR i) leptin mRNA and protein levels in PVAT, ii) the effect of leptin and PVAT on contractile responses, and iii) leptin-induced relaxation and NO production. Leptin mRNA and protein expression were signifcantly lower in PVAT from SHR. Concentration-response curves to angiotensin II were significantly blunted in presence of PVAT as well as by exogenous leptin (10-9 M) only in WKY. This anticontratile effect was endothelium-dependent. Vasodilatation induced by leptin was smaller in SHR than in WKY, and was also endothelium-dependent. Moreover, release of endothelial NO in response to acute leptin was higher in WKY compared to SHR, but completely abolished in the absence of endothelium. In conclusion, the reduced anticontractile effect of PVAT in SHR might be attributed to a reduced PVAT-derived leptin and to an abrogated effect of leptin on endothelial NO release probably due to an impaired activation of eNOS.